MENUJU SOSIOLOGI PROFETIK - Husnul Muttaqin (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2015)
Modern social sciences, including sociology, believe that religion is outside the world of science. The growth of the sciences is characterized by their secular perspectives. On the other side, the idea of islamization of social sciences is trapped in the dichotomy between secular social sciences and Islamic social sciences. In this article, the writer discuss an alternative paradigm of the integration between social science (Sociology) and religion. Based on the idea of Prophetic Social Science proposed by Kuntowijoyo, the writer states the importance of an alternative paradigm to develop sociology, called Prophetic Sociology. Prophetic Sociology is constructed based on three fundamental and integral pillars: humanization, liberation and transcendence.